Innovations in electrical stimulation harness neural plasticity to restore motor function. Issue 4 (9th April 2019) - Peng, Xiaoyu; Hickman, Jordan L; Bowles, Spencer G; Donegan, Dane C; Welle, Cristin G
Novel technology and stimulation paradigms allow for closed-loop implementation of neurostimulation systems with unprecedented spatiotemporal precision. In turn, precise, closed-loop neurostimulation appears to preferentially drive neural plasticity in motor networks, promoting neural repair. Recent clinical studies demonstrate that electrical stimulation can drive neural plasticity in damaged motor circuits, leading to meaningful functional improvement for users. Future advances in these areas hold promise for the treatment of a wide range of motor systems disorders.